The Effect of High Intensity Interval Training on the Cardiovascular Endurance of Futsal Players at SMAN 1 Dompu in 2023 - Nurdin Nurdin (Jurnal Ilmiah Mandala Education (JIME), 2025)
This study aims to determine the effect of high intensity interval training on the cardiovascular endurance of SMAN 1 Dompu futsal players in 2023. This study is a quasi-experimental study using a variety of HIIT exercises to improve cardiovascular endurance with a design of "one group pre test post test design" which is to provide pre test to the team and treatment and end with a post test to find out the results. The population in this study was the SMAN 1 Dompu futsal team which amounted to 15 participants. The sample from this study was taken from the entire population. The instruments used HIIT workouts. Data analysis using t-test. The results of the t-test analysis show: There is an effect of HIIT training on the cardiovascular endurance of futsal players of SMAN 1 Dompu, because tcalculate | -6,213 | > ttable = 2.14 and significance level of 0.000 < 0.05. Based on the results of this study, it can be concluded that cardiovascular endurance training using HIIT provides an increase in cardiovascular endurance of SMAN 1 Dompu futsal players.